Pengaruh Praktek Kerja Industri (Prakerin), Keterampilan Siswa dan Self Efficacy Terhada Kesiapan Memasuki Dunia Kerja Siswa Administrasi Perkantoran SMK Negeri Bisnis dan Manajemen Kota Padang. - Stevani Stevani; Yulhendri Yulhendri (Jurnal Kajian Pendidikan Ekonomi, 2014)
The purpose of this research is to analyze the effect of (1) intrnship to the skills of students (2) to the effect of intrnship and the skills of students to the students' self efficacy (3) to the effect of intrnship, the skills of students, and self efficacy to the work readiness students of SMK N Busines and Management Padang. This research is descriptive associative. The study population was all students in class XII SMK N Business and Management Padang in the academic year 2013/2014, totaling 130 people have followed the industry practice (intrnship), with the sampling technique was propotional random sampling. The technique of data analysis was descriptive analysis, classical assumtion test, test for normality and homogenety, path analysis, and hypotesis testing using the F test and t test. The results showed that (1) there was a significant influance on the intrnship to the skills of students (2)there was a significant influance on the the effect of intrnship and the skills of students to the students' self efficacy (3) there was a significant influance on the the effect of intrnship, the skills of students, and self efficacy to the work readiness students of SMK N Busines and Management Padang. Based on the above results it can be students of SMK N Busines and Managemen become better prepared to  the work readiness.   Kata Kunci : Intrnship, The Skills Of Students, Self Efficacy And Work Readiness